Topical Use of Fluorides for Caries Control - Pessan, Juliano Pelim [UNESP]; Toumba, Kyriacos Jack; Rabelo Buzalaf, Marilia Afonso; Buzalaf, MAR (Karger, 2011)
Since the early findings on the protective effects of fluoride present in drinking water upon caries incidence and prevalence, intensive research has been conducted in order to determine the benefits, safety, as well as the cost-effectiveness of other modalities of fluoride delivery. The present chapter reviews the various forms of topical fluoride use - professionally and self-applied - with special emphasis on clinical efficacy and possible side effects. The most widely used forms of fluoride delivery have been subject of several systematic reviews, providing strong evidence supporting the use of dentifrices, gels, varnishes and mouth rinses for the control of caries progression. Dentifrices with fluoride concentrations of 1,000 ppm and above have been shown to be clinically effective in caries prevention when compared to a placebo treatment, but the evidence regarding formulations with 450-550 ppm is still subject of debate. Therefore, the recommendation for low-fluoride dentifrice use must take into account both risks and benefits. The evidence for the combined use of two modalities of fluoride application in comparison to a single modality is still inconsistent, implying that more studies with adequate methodology are needed to determine the real benefits of each method. Considering the currently available evidence and risk-benefit aspects, it seems justifiable to recommend the use of fluoridated dentifrices to individuals of all ages, and additional fluoride therapy should also be targeted towards individuals at high caries risk. Copyright (C) 2011 S. Karger AG, Basel